2015
DOI: 10.4238/2015.september.22.25
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hormonal equilibrium linked to bamboo culm development

Abstract: ABSTRACT. Moso bamboo (Phyllostachys heterocycla) is the most important bamboo species in China and is famous for its fast-growing culms. To investigate the possible relationship between internode development and endogenous hormones, the concentrations of indole-3-acetic acid (IAA), zeatin riboside (ZR), gibberellins (GA 3 ), and abscisic acid (ABA) were analyzed in culm samples from plants at different developmental stages during a single growing season and, at the same time, anatomical structure was closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Bamboo is well known for its rapid growth and high level of woodiness. At the cellular level, the fast growth of the bamboo culm is mainly due to cell elongation and division [ 24 ]. Auxin is one of the well-known phytohormones that controls cell division and expansion [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboo is well known for its rapid growth and high level of woodiness. At the cellular level, the fast growth of the bamboo culm is mainly due to cell elongation and division [ 24 ]. Auxin is one of the well-known phytohormones that controls cell division and expansion [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moso bamboo is one of the most important non-timber forest products in the world, due to its great economic, cultural, and environmental value [ 23 ]. Moso bamboo is famous for its fast-growing culms which were controlled by cell division and cell elongation [ 24 ]. Although the mechanisms that control plant cell number and size are not fully understood, phytohormones, especially auxin have important roles in the regulation and coordination of plant cell proliferation and elongation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A later proteomics study showed seven protein spots involved in hormone biosynthesis during shoot development [ 11 ]. The concentration of endogenous GA 3 , one of most common bioactive forms of gibberellic acid [ 12 ], displays bimodal variation when the above-ground heights grow from 0.05 m to 12 m in moso bamboo [ 11 , 13 , 14 ]. The extensibility of moso bamboo cell walls is a key factor in moso bamboo’s growth, as they allow grow to great heights due to the two primary components of bamboo walls, cellulose and lignin [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid growth is largely achieved through cell division and the elongation of the intercalary meristem at the basal part of each node (Inze & De Veylder, 2006). Specifically, cell division is predominant during the initial stages of rapid growth, and cell elongation largely accounts for the rapid late elongation of bamboo (Wang et al, 2015). The biosynthesis and signaling of brassinosteroids (BRs) (Wang et al, 2019), auxins (AUXs) (Wang et al, 2017), and gibberellic acids (GAs) (Zhang et al, 2018) appear to regulate cell division, differentiation, and elongation, which are key for the rapid growth of bamboo species.…”
Section: Introductionmentioning
confidence: 99%